Evaluasi Dan Perbaikan Aplikasi ONLINE RSAM Dengan Menggunakan Metode Usability Testing Dan System Usability Scale (SUS) Pada Rumah Sakit Anwar Medika Sidoarjo - Dhuha Rizky Ramadhan; Retno Indah Rokhmawati; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Anwar Medika Hospital, Sidoarjo is one of the service agencies in the health sector which has 17 health service polyclinics and 22 disease specialist polyclinics. The total number of patients at Anwar Medika Hospital, Sidoarjo is approximately 15,000 and has 49 doctors. Anwar Medika Hospital, Sidoarjo develops hospital information facilities and has the main feature of booking outpatient queues in a mobile application called Online RSAM (Online Hospital Anwar Medika) which has a function to provide information related to Anwar Medika Hospital services. In its use, several problems were found related to the usability of the application which was tested through usability testing metric effectiveness. Efficiency and satisfaction with the System usability scale (SUS). The first evaluation found 6 problems related to the 5 given task scenarios, the next step was to improve the application interface according to the problems obtained based on the respondent's behavior, interviews and guidelines. The next stage is second evaluation based on the interface recommendations that have been made and then comparing the results of the second evaluation with the first evaluation. The results of the second evaluation based on recommendations for improving the application interface can increase the effectiveness matrix to 100% from the previous 96%, the efficiency metric increased from 0.06 goal / s to 0.08 goal / s and the satisfaction metric increased user satisfaction based on the SUS score of 66. to 79 so that it is in the "acceptable" position in terms of acceptability ranges.